Дослідження кінематики універсального регулятора швидкості колісного трактора - Харак, Р. М.; Сакало, В. М.; Лихвенко, С. П.; Kharak, R.; Sakalo, V.; Lykhvenko, S. (КНТУ, 2013)
Запропонована методика дослідження кінематики універсального регулятора паливного насоса розподільчого типу з автоматичним переключенням режимності роботи трактора ХТЗ – 150К-03. The proposed method studies the kinematics universal regulator fuel pump distribution type with automatic switchover modes tractor KhTZ-150K-03. Kinematic analysis was conducted using the closed vector paths. As a result, the rational move anchors electromagnets mode switching mechanism regulating universal regulator. To determine the parameters of rational mechanism links the automated switching modes tractor engine is to study the kinematics of the universal controller. Found that progress anchors electromagnets – 3.34 mm, internal lever controls the fuel supply – 4.1mm, turning lever – 28.4 mm. The proposed mechanism for automatic switching modes allows the diesel engine management to simplify the process and reduce operational fuel consumption by 6-8 % in the transport operations.
Research kinematic characteristics of universal regulator movement of tractor trailers
Keywords: трактор; дизель; регулятор; механізм; кінематичний аналіз; електромагніт; паливна економічність; tractor; diesel; regylator; mehanism; kinematic analysis; electromagnet; fuel economy